Graphite composite material and preparation method and application thereof

By forming a bilayer structure of amorphous carbon material and a porous structural graphite material on the surface of the graphite matrix, the problem of unsatisfactory electrochemical performance of modified graphite materials is solved, and graphite composite materials with high capacity, high first efficiency and good cycle rate performance are achieved.

CN119601629APending Publication Date: 2025-03-11JIANGXI ZICHEN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411766508.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The electrochemical properties of existing modified graphite materials are not ideal, limiting their application in the consumer electronics market.

Method used

By providing a first material layer and a second material layer on the surface of the graphite substrate, the first material layer consists of amorphous carbon material doped with a first nitrogen element, and the second material layer consists of a graphite material, has a porous structure and is doped with a second nitrogen element.

Benefits of technology

The capacity, first-effect, cycle performance and rate performance of graphite composite materials have been significantly improved, and the energy storage capacity and safety performance of the battery have been enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601629A_ABST
    Figure CN119601629A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a graphite composite material and a preparation method and application thereof. The graphite composite material comprises a base material layer and a coating layer, and the coating layer comprises a first material layer and a second material layer; the base material layer comprises graphite; the first material layer comprises an amorphous carbon material, and the amorphous carbon material is doped with a first nitrogen element; the second material layer comprises a graphite material, and the graphite material has a porous structure and is doped with a second nitrogen element; the concentration of the first nitrogen element is greater than that of the second nitrogen element. According to the graphite composite material, the first material layer can ensure the reversible capacity and the rate capability of the material; the graphitization degree of the carbon material in the second material layer is high, the irreversible capacity can be reduced, the low nitrogen concentration is beneficial to improving the conductivity, and the porous structure can shorten an ion diffusion channel, so that the energy storage capacity and the rate capability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a graphite composite material and a preparation method and application thereof. Background Art

[0002] Graphite has become the most widely used negative electrode material for lithium-ion batteries due to its stable performance and low (de)lithiation potential. However, its low theoretical capacity (372mAh / g) and poor rate performance have greatly limited its application in the rapidly growing consumer electronics market. Therefore, in order to improve the electrochemical properties of graphite negative electrode materials, researchers have conducted a lot of research. At present, researchers mainly use surface treatment, surface coating and element doping methods to modify graphite negative electrodes in order to improve their own structural shortcomings and improve battery performance. However, the electrochemical properties of the modified graphite materials are not ideal.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] One object of the present invention is to provide a graphite composite material to solve the technical problem that the electrochemical performance of the modified graphite material is not ideal. The graphite composite material of the present invention is provided with a first material layer and a second material layer to improve the capacity and first efficiency, and improve the cycle performance and rate performance of the battery.

[0005] Another object of the present invention is to provide a method for preparing the graphite composite material, which can form a suitable first material layer and a second material layer on the surface of the graphite substrate through the coordination of various steps to coordinately improve the comprehensive electrochemical properties of the graphite composite material.

[0006] Another object of the present invention is to provide a negative electrode sheet as described above.

[0007] Another object of the present invention is to provide a battery as described above.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] A graphite composite material comprises a base material layer and a coating layer, wherein the coating layer comprises a first material layer located on the surface of the base material and a second material layer located on the surface of the first material layer; the base material layer comprises graphite; the first material layer comprises an amorphous carbon material, and the amorphous carbon material is doped with a first nitrogen element; the second material layer comprises a graphite material, the graphite material has a porous structure, and is doped with a second nitrogen element; the concentration of the first nitrogen element is greater than the concentration of the second nitrogen element.

[0010] In some embodiments, the particle size of the base material layer is 5 to 30 μm.

[0011] In some embodiments, the coating layer has a thickness of 5 to 100 nm; and the thickness ratio of the first material layer to the second material layer is (5 to 20):1.

[0012] A method for preparing a graphite composite material comprises the following steps:

[0013] The mixture of nitrogen-containing precursor and graphite is subjected to a first heat treatment to obtain a first material; the first material and a metal catalyst are subjected to a grinding treatment, a second heat treatment and an acid washing treatment to obtain a graphite composite material.

[0014] In some embodiments, the nitrogen-containing precursor includes at least one of melamine, urea, thiourea, guanidine and dicyandiamide.

[0015] In some embodiments, the graphitization degree g of the graphite satisfies: 90%≤g<100%.

[0016] In some embodiments, the mass ratio of the nitrogen-containing precursor to the graphite is (0.3-3):1.

[0017] In some embodiments, the temperature of the first heat treatment is 500-650° C., and the time of the first heat treatment is 1-4 hours.

[0018] In some embodiments, the heating rate of the first heat treatment is 1-5° C. / min.

[0019] In some implementations, the method further includes cooling, grinding and screening the material obtained by the first heat treatment, wherein the screening is through a 325 mesh sieve.

[0020] In some embodiments, the metal catalyst includes at least one of zinc powder, nickel powder, manganese powder, molybdenum powder, magnesium powder and cobalt powder.

[0021] In some embodiments, the mass ratio of the metal catalyst to the first material is (0.5-1):(1-3).

[0022] In some embodiments, the temperature of the second heat treatment is 680-900° C., and the time of the second heat treatment is 1-4 hours;

[0023] In some embodiments, the heating rate of the second heat treatment is 1-5° C. / min.

[0024] In some embodiments, the acid used for pickling includes at least one of nitric acid, hydrochloric acid and hydrofluoric acid. The acid concentration of the pickling is 1 to 6 mol / L.

[0025] In some embodiments, the method further comprises: washing and drying the material obtained after the acid washing, wherein the drying temperature is 80 to 200° C. and the drying time is 8 to 13 hours.

[0026] A negative electrode sheet comprises the graphite composite material or the graphite composite material prepared by the graphite composite material preparation method.

[0027] A battery comprises the negative electrode sheet.

[0028] An electrical device comprises the battery.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) In the graphite composite material of the present invention, the amorphous carbon material in the first material layer has a larger interlayer spacing than the graphite matrix, thereby promoting the electrode reaction process, which enables lithium ions to be randomly transmitted inside and promotes the rapid migration of lithium ions, thereby showing good rate performance. In addition, the amorphous carbon material shows a smaller volume change during the charge / discharge process, and thus has good cycle performance. In addition, the nitrogen atoms in the carbon lattice can play a role in adjusting the electronic structure of graphite, so the first nitrogen element doping can effectively improve the reversible capacity and rate performance of the carbon anode; the graphitization degree of the carbon material in the second material layer is higher than that of the first amorphous carbon material, which can reduce the disorder of the amorphous carbon, which is beneficial to reducing the irreversible capacity. The reduction of the nitrogen content in the second material layer is more beneficial to improving the electrical conductivity of the material. Its porous structure can shorten the ion diffusion channel, promote the penetration of electrolyte between carbon layers, and is beneficial to electrolyte penetration and ion adsorption, thereby improving the energy storage capacity and rate performance.

[0031] (2) The preparation method of the graphite composite material of the present invention first uses a nitrogen-containing precursor to mix with graphite and performs a first heat treatment to form a carbon nitride amorphous carbon layer on the surface of the graphite to obtain a first material; further, the first material is catalytically graphitized and etched using a metal catalyst. During the heating process, the metal catalyst reacts with aminocyanic acid to form aminocyanic acid-metal compounds, thereby taking away additional nitrogen atoms, thereby gradually graphitizing the carbon nitride and increasing its conductivity. Finally, the metal powder catalyst is removed by acid washing to form a first material layer and a second material layer. The catalytic graphitization of the metal catalyst can significantly reduce the disorder of the amorphous carbon in the second material layer, which is beneficial to reducing the irreversible capacity. Its nitrogen content is significantly reduced, so that the concentration of the second nitrogen element in the second material layer is lower than the concentration of the first nitrogen element in the first material layer, which greatly improves the conductivity of the composite material; in addition, the final pickling process produces a large number of suitable pore size distributions on the surface and bulk of the negative electrode material, and the porous structure can easily contact each other in parallel or series. Therefore, the shortened ion diffusion channel promotes the penetration of the electrolyte between the carbon layers, which is beneficial to the electrolyte penetration and ion adsorption, thereby improving the energy storage capacity and rate performance. This method has a wide range of raw materials, low prices, simple experimental operation technology, and high feasibility of large-scale production.

[0032] (3) The battery of the present invention has the characteristics of high capacity and high initial efficiency, good cycle performance and rate performance, and high safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 The X-ray diffraction pattern (XRD) of the graphite composite material and graphite of Example 1 of the present invention;

[0035] Figure 2 This is a scanning electron microscope image (SEM) of the graphite composite material in Example 1 of the present invention;

[0036] Figure 3 This is a scanning electron microscope image of the graphite in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0038] According to one aspect of the present invention, the present invention relates to a graphite composite material, comprising a base material layer and a coating layer, the coating layer comprising a first material layer located on the surface of the base material and a second material layer located on the surface of the first material layer; the base material layer comprises graphite; the first material layer comprises an amorphous carbon material, and the amorphous carbon material is doped with a first nitrogen element; the second material layer comprises a graphite material, the graphite material has a porous structure, and is doped with a second nitrogen element; the concentration of the first nitrogen element is greater than the concentration of the second nitrogen element.

[0039] In the graphite composite material of the present invention, the presence of nitrogen in the coating layer can improve the electronic configuration of carbon atoms in the original graphite structure and increase the conductivity of the original carbon network. Nitrogen-doped carbon tends to provide higher adsorption energy than the original undoped carbon, and edge nitrogen doping can effectively enhance the adsorption of Li + In addition, edge nitrogen doping can generate abundant defect sites for adsorption of Li + active sites, increasing the reversible capacity while facilitating the rapid diffusion of lithium ions; wherein, the amorphous carbon material in the first material layer has a larger interlayer spacing than the graphite matrix, thereby promoting the electrode reaction process, which enables lithium ions to be randomly transmitted internally and promotes the rapid migration of lithium ions, thereby showing good rate performance. In addition, the amorphous carbon material shows a small volume change during the charge / discharge process, and therefore has good cycle performance. In addition, the nitrogen atoms in the carbon lattice can play a role in adjusting the electronic structure of graphite, so the first nitrogen element doping can effectively improve the reversible capacity and rate performance of the carbon anode; the carbon material in the second material layer has a higher degree of graphitization than the amorphous carbon material, which can reduce the disorder of amorphous carbon, which is beneficial to reducing the irreversible capacity. The reduction in the nitrogen content in the second material layer is more conducive to improving the electrical conductivity of the material, and its porous structure can shorten the ion diffusion channel, promote the penetration of electrolytes between carbon layers, and is beneficial to electrolyte penetration and ion adsorption, thereby improving the energy storage capacity and rate performance.

[0040] In some embodiments, the particle size of the base material layer is 5 to 30 μm, such as 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc., or any range between the two. The thickness of the coating layer is 5 to 100 nm, such as 5 nm, 10 nm, 20 nm, 30 nm, 50 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc., or any range between the two. The thickness ratio of the first material layer and the second material layer is (5 to 20): 1, such as 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, 12: 1, 15: 1, 18: 1 or 20: 1, etc. The base material layer of the present invention has a suitable particle size, the coating layer has a suitable thickness, and the first material layer and the second material layer have a suitable thickness ratio, which is more conducive to improving the electrochemical properties of the graphite composite material.

[0041] According to another aspect of the present invention, the present invention also relates to a method for preparing a graphite composite material, comprising the following steps:

[0042] The mixture of the nitrogen-containing precursor and graphite is subjected to a first heat treatment to obtain a first material; the first material and the metal catalyst are subjected to a grinding treatment, a second heat treatment and an acid washing treatment to obtain a graphite composite material.

[0043] The preparation method of the graphite composite material of the present invention comprises the following steps: firstly, mixing a nitrogen-containing precursor with graphite and subjecting the graphite to a first heat treatment to form a carbon nitride amorphous carbon layer on the surface of the graphite to obtain a first material; further, catalytic graphitization and etching of the first material are performed using a metal catalyst, wherein the metal catalyst reacts with aminocyanic acid during heating to generate aminocyanic acid-metal compound, thereby taking away extra nitrogen atoms, thereby gradually graphitizing the carbon nitride and increasing its conductivity; finally, acid washing is used to remove the metal powder catalyst to form a first material layer and a second material layer. The catalytic graphitization of the metal catalyst can significantly reduce the disorder of the amorphous carbon in the second material layer, which is beneficial to reducing the irreversible capacity. Its nitrogen content is significantly reduced, so that the concentration of the second nitrogen element in the second material layer is lower than the concentration of the first nitrogen element in the first material layer, which greatly improves the conductivity of the composite material; in addition, the final pickling process produces a large number of suitable pore size distributions on the surface and bulk of the negative electrode material, and the porous structure can easily contact each other in parallel or series. Therefore, the shortened ion diffusion channel promotes the penetration of the electrolyte between the carbon layers, which is beneficial to the electrolyte penetration and ion adsorption, thereby improving the energy storage capacity and rate performance. This method has a wide range of raw materials, low prices, simple experimental operation technology, and high feasibility of large-scale production.

[0044] In some embodiments, the present invention further relates to a nitrogen-containing precursor comprising at least one of melamine, urea, thiourea, guanidine and dicyandiamide. For example, a combination of melamine and urea, a combination of urea and thiourea, a combination of urea, thiourea and dicyandiamide, etc. The above materials have simple structures, high nitrogen content, high doping efficiency, wide sources, environmental friendliness and low cost.

[0045] In some embodiments, the graphitization degree g of the graphite satisfies: 90%≤g<100%, including but not limited to 90%, 92%, 94%, 96%, 98%, etc., or any range between the two. In some embodiments, the graphite is artificial biomass graphite, which has a wide range of raw materials.

[0046] In some embodiments, the mass ratio of the nitrogen-containing precursor to graphite is (0.3-3):1, including but not limited to 0.3:1, 0.5:1, 0.6:1, 0.8:1, 1:1, 1.5:1, 2:1, 2.5:1 or 3:1, or any range between the two. The nitrogen-containing precursor and graphite in the present invention adopt a suitable mass ratio to ensure that the total coating layer obtained has a suitable thickness, which is beneficial to improve the specific capacity and initial coulomb efficiency of the graphite composite material. If the nitrogen-containing precursor is used in a low proportion, the coating layer is too thin, and the improvement effect is not obvious; if the nitrogen-containing precursor is used in a high proportion, the coating layer is too thick, which will also reduce the specific capacity and initial coulomb efficiency of the graphite composite material.

[0047] In some embodiments, the temperature of the first heat treatment is 500-650°C, including but not limited to 500°C, 520°C, 550°C, 580°C, 600°C, 620°C, 640°C, 650°C, etc., or any range between the two. The time of the first heat treatment is 1-4h, including but not limited to 2h, 2.5h, 3h, 3.5h or 4h, etc., or any range between the two. The heating rate of the first heat treatment is 1-5°C / min, for example, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, etc., or any range between the two. The present invention adopts suitable first heat treatment conditions to ensure the coating effect of amorphous carbon nitride coated graphite.

[0048] In some embodiments, the method further comprises: cooling the material obtained from the first heat treatment, grinding and sieving the material after cooling to room temperature, and sieving the material to pass through a 325-mesh sieve.

[0049] In some embodiments, the metal catalyst includes at least one of zinc powder, nickel powder, manganese powder, molybdenum powder, magnesium powder and cobalt powder. For example, zinc powder and nickel powder, nickel powder and manganese powder, or manganese powder, magnesium powder and cobalt powder, etc. In some embodiments, the mass ratio of the metal catalyst to the first material is (0.5-1): (1-3), such as 0.5:1, 0.8:1.5, 0.8:2, 1:2.5 or 1:3, etc. The present invention uses a metal catalyst with a suitable dosage ratio to further improve the graphitization degree of the amorphous carbon material in the second material layer, reduce the size of the irreversible capacity, and generate a suitable number of pore structures. If the dosage ratio of the catalyst is too high, it will increase the difficulty of pickling and purification and increase production costs, and it is easy to cause the specific surface area of ​​the carbon material to be too large, so that the first coulomb efficiency of the carbon material is low. If the dosage ratio of the catalyst is too low, the catalytic conversion effect is poor, and the pore structure is too small, which is not conducive to the rapid migration of the electrolyte.

[0050] In some embodiments, the temperature of the second heat treatment is 680-900°C, including but not limited to 680°C, 700°C, 750°C, 800°C, 820°C, 850°C, 880°C, 900°C, etc., or any range between the two. The time of the second heat treatment is 1-4h, including but not limited to 2h, 2.5h, 3h, 3.5h or 4h, etc., or any range between the two. The heating rate of the second heat treatment is 1-5°C / min, such as 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min or 5°C / min, etc. The present invention adopts suitable second heat treatment conditions to ensure the coating effect of the final coating layer and improve the electrochemical properties of the graphite composite material.

[0051] In some embodiments, the pickling acid includes at least one of nitric acid, hydrochloric acid and hydrofluoric acid, and the acid concentration is 1 to 6 mol / L, such as 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L or 6 mol / L, or any range between the two. The present invention uses an acid solution of a suitable concentration for washing, thereby better removing metal elements and forming a second material layer with a suitable porous structure.

[0052] In some embodiments, the method further includes: washing and drying the material obtained after acid washing, the drying temperature is 80-200°C, for example, 100°C, 110°C, 130°C, 150°C, 180°C, 200°C, etc., and the drying time is 8-13h, for example, 8h, 9h, 10h, 11h, 12h or 13h, etc.

[0053] In one embodiment, a method for preparing a graphite composite material comprises the following steps:

[0054] (a) subjecting a mixture of a nitrogen-containing precursor and graphite to a first heat treatment to obtain a first material, wherein the nitrogen-containing precursor comprises at least one of melamine, urea, thiourea, guanidine and dicyandiamide; the graphitization degree g of the graphite satisfies: 90%≤g<100%; the mass ratio of the nitrogen-containing precursor to the graphite is (0.3-3):1; the temperature of the first heat treatment is 500-650°C, the time of the first heat treatment is 1-4h; the heating rate of the first heat treatment is 1-5°C / min; and the material obtained by the first heat treatment is cooled, ground and sieved through a 325-mesh sieve.

[0055] (b) grinding the first material and the metal catalyst, wherein the metal catalyst includes at least one of zinc powder, nickel powder, manganese powder, molybdenum powder, magnesium powder and cobalt powder, and the mass ratio of the metal catalyst to the first material is (0.5-1):(1-3); performing a second heat treatment on the ground material, the temperature of the second heat treatment is 680-900°C, the time of the second heat treatment is 1-4h, and the heating rate of the second heat treatment is 1-5°C / min; then performing an acid pickling treatment, the acid used for the pickling includes at least one of nitric acid, hydrochloric acid and hydrofluoric acid, the acid concentration of the pickling is 1-6mol / L, and the material obtained after the pickling is dried at a drying temperature of 80-200°C and a drying time of 8-13h to obtain a graphite composite material;

[0056] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising the above-mentioned graphite composite material, or a graphite composite material prepared by the above-mentioned method for preparing the graphite composite material.

[0057] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode material layer located on the surface of the negative electrode current collector, wherein the negative electrode material layer comprises the above-mentioned graphite composite material, a conductive agent and a binder. In some embodiments, the mass ratio of the graphite composite material, the conductive agent and the binder is (92-96): (4-6): (1-3).

[0058] According to another aspect of the present invention, the present invention also relates to a battery, comprising the above-mentioned negative electrode sheet.

[0059] The battery of the present invention has the characteristics of high capacity and high initial efficiency, good cycle performance and rate performance, and high safety performance.

[0060] In some embodiments, the battery of the present invention includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte.

[0061] According to another aspect of the present invention, the present invention also relates to an electric device, comprising the above-mentioned battery. The electric device includes a portable device, an electric car, and the like.

[0062] The following is further explained in conjunction with specific embodiments and comparative examples.

[0063] Example 1

[0064] A method for preparing a graphite composite material comprises the following steps:

[0065] (1) Melamine and dicyandiamide are mixed in a mass ratio of 1:1, and then the mixture is mixed with graphite in a mass ratio of 1:1, wherein the graphitization degree of the graphite is 94%. After being mixed evenly, the temperature is increased to 550° C. at a rate of 2° C. / min and kept at this temperature for 2 hours. After cooling, the mixture is ground and passed through a 325 sieve to obtain a first material.

[0066] (2) Then, the obtained first material and metal nickel powder are mixed evenly in a ratio of 1:1, and the temperature is raised to 700°C at a rate of 3°C / min, and kept at this temperature for 2 hours. After cooling, the mixture is washed with an excess of hydrochloric acid solution, the concentration of which is 3 mol / L. Then, the mixture is washed with sufficient deionized water until neutral, and vacuum dried at 100°C for 10 hours. After grinding and sieving, a graphite composite material is obtained.

[0067] Example 2

[0068] A method for preparing a graphite composite material comprises the following steps:

[0069] (1) Urea and graphite are mixed in a mass ratio of 1:2, the graphitization degree of the graphite is 94%, and after being mixed evenly, the temperature is raised to 550°C at a rate of 2°C / min and kept at this temperature for 3 hours. The mixture is ground and passed through a 325-mesh sieve to obtain a first material.

[0070] (2) Then, the obtained first material and metal zinc powder are mixed in a mass ratio of 1:2. After being mixed evenly, the temperature is raised to 700°C at a rate of 3°C / min and kept at this temperature for 2 hours. After cooling, the mixture is washed with an excess of hydrochloric acid solution, the concentration of which is 3 mol / L. Then, the mixture is washed with sufficient deionized water until it becomes neutral, and vacuum dried at 100°C for 10 hours. After grinding, a graphite composite material is obtained.

[0071] Example 3

[0072] A method for preparing a graphite composite material comprises the following steps:

[0073] (1) Dicyandiamide and graphite are mixed in a mass ratio of 1:3, the graphitization degree of the graphite is 94%, and after being mixed evenly, the temperature is raised to 550° C. at a rate of 2.5° C. / min and kept at that temperature for 4 hours. After cooling, the mixture is ground and passed through a 325 sieve to obtain a first material.

[0074] (2) Then, the obtained first material and metal magnesium powder are mixed evenly in a ratio of 1:1, and the temperature is raised to 700°C at a rate of 3°C / min, and kept at this temperature for 2 hours. After cooling, the mixture is washed with an excess of hydrochloric acid solution, the concentration of which is 3 mol / L. Then, the mixture is washed with sufficient deionized water until neutral, and vacuum dried at 100°C for 10 hours. After grinding and sieving, a graphite composite material is obtained.

[0075] Example 4

[0076] A method for preparing a graphite composite material comprises the following steps:

[0077] (1) Dicyandiamide and graphite are mixed in a mass ratio of 1:3, the graphitization degree of the graphite is 94%, and after being mixed evenly, the temperature is raised to 550° C. at a rate of 2.5° C. / min and kept at that temperature for 4 hours. After cooling, the mixture is ground and passed through a 325 sieve to obtain a first material.

[0078] (2) Then, the obtained first material and metal manganese powder are mixed evenly in a ratio of 1:1, and the temperature is raised to 700°C at a heating rate of 3°C / min, and the temperature is kept for 2 hours. After cooling, the mixture is washed with an excess of hydrochloric acid solution, and the concentration of the hydrochloric acid is 3 mol / L. Then, the mixture is washed with sufficient deionized water until neutral, and vacuum dried at 100°C. After grinding and sieving, a graphite composite material is obtained.

[0079] Example 5

[0080] (1) Melamine, dicyandiamide and urea are mixed in a mass ratio of 1:1:1, and then the mixture is mixed with graphite in a mass ratio of 1:1, wherein the graphitization degree of the graphite is 94%. After being mixed evenly, the temperature is increased to 600° C. at a rate of 4° C. / min and kept at this temperature for 1.5 hours. After cooling, the mixture is ground and passed through a 325 sieve to obtain a first material.

[0081] (2) Then, the obtained first material is mixed evenly with metal nickel powder and metal magnesium powder in a ratio of 1:0.5:0.5, and the temperature is raised to 780°C at a heating rate of 4°C / min, and kept warm for 1.5 hours. After cooling, the mixture is washed with an excess of hydrochloric acid solution, the concentration of which is 3 mol / L. Then, the mixture is washed with sufficient deionized water until neutral, and vacuum dried at 150°C for 9 hours. After grinding and sieving, a graphite composite material is obtained.

[0082] Example 6

[0083] A method for preparing a graphite composite material comprises the following steps:

[0084] (1) Melamine and dicyandiamide are mixed in a mass ratio of 1:1, and then the mixture is mixed with graphite in a mass ratio of 1:1, wherein the graphitization degree of the graphite is 94%. After being mixed evenly, the temperature is increased to 650° C. at a rate of 5° C. / min and kept at that temperature for 1 hour. After cooling, the mixture is ground and passed through a 325 sieve to obtain a first material.

[0085] (2) Then, the obtained first material and metal nickel powder are mixed evenly in a ratio of 1:1, and the temperature is raised to 900°C at a rate of 5°C / min, and kept at this temperature for 1 hour. After cooling, the mixture is washed with an excess of hydrochloric acid solution, the concentration of which is 6 mol / L. Then, the mixture is washed with sufficient deionized water until neutral, and vacuum dried at 200°C for 8 hours. After grinding and sieving, a graphite composite material is obtained.

[0086] Example 7

[0087] A method for preparing a graphite composite material comprises the following steps:

[0088] (1) Melamine and dicyandiamide are mixed in a mass ratio of 1:1, and then the mixture is mixed with graphite in a mass ratio of 1:1, wherein the graphitization degree of the graphite is 94%. After being mixed evenly, the temperature is raised to 500° C. at a rate of 3° C. / min and kept at this temperature for 4 hours. After cooling, the mixture is ground and passed through a 325 sieve to obtain a first material.

[0089] (2) Then, the obtained first material and metal nickel powder are mixed evenly in a ratio of 1:1, and the temperature is raised to 680°C at a rate of 3°C / min, and kept warm for 4 hours. After cooling, the mixture is washed with an excess of hydrochloric acid solution, the concentration of which is 1 mol / L. Then, the mixture is washed with sufficient deionized water until neutral, and vacuum dried at 80°C for 13 hours. After grinding and sieving, a graphite composite material is obtained.

[0090] Comparative Example 1

[0091] Graphite matrix material with a graphitization degree of 94%.

[0092] Comparative Example 2

[0093] A graphite composite material is provided, wherein a first material is obtained according to step (1) of embodiment 1. The first material comprises a graphite matrix material with a graphitization degree of 94% and an amorphous carbon material coating layer doped with nitrogen on the surface of the matrix material.

[0094] Experimental example

[0095] 1. Graph Analysis

[0096] The XRD patterns of the graphite composite material and graphite prepared in Example 1 are as follows: Figure 1As shown, the two samples show similar XRD patterns, which may have a typical hexagonal graphite structure, as evidenced by the 2θ main peak at 26.42°, which indicates that the modification process of the coating layer on the graphite does not destroy the typical structure of graphite. After coating, the (002) crystal plane diffraction intensity of the amorphous carbon-coated graphite is slightly reduced, indicating a decrease in crystallinity. The decrease in crystallinity may mean that a small change has occurred in the graphite surface morphology, that is, an amorphous surface layer has been formed. Figure 3 As shown in the figure, the surface of the original graphite is smoother; the surface of the graphite coated with the coating layer is not as smooth as the original graphite surface, but there are no protrusions, such as Figure 2 As shown, it is explained that the coating layer of the present invention does not change the spherical shape of the graphite particles and coats the graphite uniformly to form core-shell structure particles.

[0097] 2. Battery performance test

[0098] The graphite composite material prepared in each embodiment and the material of the comparative example are used as the negative electrode material, and the graphite composite material, polyvinylidene fluoride (PVDF) binder, conductive carbon black (Super P) and conductive graphite (KS-6) are weighed in a mass ratio of 94:5:1:0.2, and N-methylpyrrolidone (NMP) is used as a solvent, mixed and ball-milled for 3 hours to form a slurry. The slurry is evenly coated on a copper foil and vacuum dried at 85°C for 12 hours. A metal lithium sheet is used as the counter electrode, Celgard2000 is used as a diaphragm, 1M LiPF6 is used as an electrolyte, and the solvent is a mixture of three components of EC, DEC, and DMC with a volume fraction of 1:1:1. In an argon atmosphere, a CR2032 button battery is assembled in an anhydrous glove box and aged for 24 hours.

[0099] The test results of each battery are shown in Table 1.

[0100] Table 1 Test results

[0101] Group 0.1C discharge capacity (mAh / g) First efficiency (%) Example 1 466 95 Example 2 432 94 Example 3 411 94 Example 4 415 93 Example 5 458 94 Example 6 422 93 Example 7 402 94 Comparative Example 1 355 89 Comparative Example 2 389 91

[0102] As can be seen from Table 1, the specific capacity and first efficiency of the batteries obtained from the graphite composite materials synthesized in various embodiments of the present invention are high, with the specific capacity being above 400 mAh / g and the first efficiency being 93% and above.

[0103] The batteries prepared from the materials of Comparative Examples 1 to 2 have low specific capacity and low initial efficiency.

[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A graphite composite material, characterized in that: It comprises a base material layer and a coating layer, wherein the coating layer comprises a first material layer located on the surface of the base material and a second material layer located on the surface of the first material layer; The matrix material layer includes graphite; The first material layer includes an amorphous carbon material, and the amorphous carbon material is doped with a first nitrogen element; The second material layer includes a graphite material having a porous structure and being doped with a second nitrogen element; The concentration of the first nitrogen element is greater than the concentration of the second nitrogen element.

2. The graphite composite material according to claim 1, characterized in that The particle size of the matrix material layer is 5 to 30 μm; The coating layer has a thickness of 5 to 100 nm; The thickness ratio of the first material layer to the second material layer is (5-20):

1.

3. A method for preparing a graphite composite material, characterized in that: The following steps are involved: Performing a first heat treatment on a mixture of a nitrogen-containing precursor and graphite to obtain a first material; The first material and the metal catalyst are subjected to grinding treatment, a second heat treatment and an acid washing treatment to obtain a graphite composite material.

4. The method for preparing the graphite composite material according to claim 3, characterized in that: Contains at least one of the following features (1) to (3): (1) The nitrogen-containing precursor includes at least one of melamine, urea, thiourea, guanidine and dicyandiamide; (2) The graphitization degree g of the graphite satisfies: 90%≤g<100%; (3) The mass ratio of the nitrogen-containing precursor to the graphite is (0.3-3):

1.

5. The method for preparing the graphite composite material according to claim 3, characterized in that: Contains at least one of the following features (1) to (3): (1) The temperature of the first heat treatment is 500 to 650° C., and the time of the first heat treatment is 1 to 4 hours; (2) The heating rate of the first heat treatment is 1 to 5°C / min; (3) The method further includes cooling, grinding and screening the material obtained by the first heat treatment, wherein the screening is performed through a 325-mesh sieve.

6. The method for preparing the graphite composite material according to claim 3, characterized in that: Contains at least one of the following features (1) to (4): (1) The metal catalyst comprises at least one of zinc powder, nickel powder, manganese powder, molybdenum powder, magnesium powder and cobalt powder; (2) The mass ratio of the metal catalyst to the first material is (0.5-1):(1-3); (3) The temperature of the second heat treatment is 680 to 900° C., and the time of the second heat treatment is 1 to 4 hours; (4) The heating rate of the second heat treatment is 1 to 5°C / min.

7. The method for preparing the graphite composite material according to claim 3, characterized in that: Contains at least one of the following features (1) to (3): (1) The acid used for pickling includes at least one of nitric acid, hydrochloric acid and hydrofluoric acid; (2) The acid concentration of the pickling is 1 to 6 mol / L; (3) It also includes: washing and drying the material obtained after the acid washing, wherein the drying temperature is 80 to 200° C. and the drying time is 8 to 13 hours.

8. A negative electrode sheet, characterized in that: The invention comprises the graphite composite material according to any one of claims 1 to 2, or a graphite composite material prepared by the method for preparing the graphite composite material according to any one of claims 3 to 7.

9. A battery, characterized in that: Includes the negative electrode sheet as described in claim 8.

10. An electrical device, characterized in that: A battery comprising the battery of claim 9.